2016
DOI: 10.1158/0008-5472.can-16-0523
|View full text |Cite
|
Sign up to set email alerts
|

Acute Sensitivity of Ph-like Acute Lymphoblastic Leukemia to the SMAC-Mimetic Birinapant

Abstract: Ph-like acute lymphoblastic leukemia (ALL) is a genetically defined high-risk ALL subtype with a generally poor prognosis. In this study, we evaluated the efficacy of birinapant, a small molecule mimetic of the apoptotic regulator SMAC, against a diverse set of ALL subtypes. Birinapant exhibited potent and selective cytotoxicity against B-cell precursor ALL (BCP-ALL) cells that were cultured ex vivo or in vivo as patient-derived tumor xenografts (PDX). Cytotoxicity was consistently most acute in Ph-like BCP-AL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 51 publications
8
41
1
Order By: Relevance
“…They performed a global gene expression profile of ALL-PDTX, 6 responders and 6 nonresponders, to birinapant (SMAC mimetic). Using this approach, they found that the efficacy of birinapant strongly depends on TNFα (or other inflammatory cytokines) expression, which could be used as predictive biomarker for birinapant response in ALL patients [63]. Since the capacity to positively engraft breast cancers into host mice depends on the aggressiveness of the primary tumor, Moon et al were able to show a specific prognostic signature linked to TNBC PDTX engraftment predicting patient survival [64].…”
Section: Pdtx In Translational Cancer Research Forestall Treatment Famentioning
confidence: 99%
“…They performed a global gene expression profile of ALL-PDTX, 6 responders and 6 nonresponders, to birinapant (SMAC mimetic). Using this approach, they found that the efficacy of birinapant strongly depends on TNFα (or other inflammatory cytokines) expression, which could be used as predictive biomarker for birinapant response in ALL patients [63]. Since the capacity to positively engraft breast cancers into host mice depends on the aggressiveness of the primary tumor, Moon et al were able to show a specific prognostic signature linked to TNBC PDTX engraftment predicting patient survival [64].…”
Section: Pdtx In Translational Cancer Research Forestall Treatment Famentioning
confidence: 99%
“…When compared to other pre-B ALL subtypes, Ph-like ALL has the following characteristic features: (1) higher median leukocyte count at presentation, (2) higher median levels of MRD at the end of induction therapy, (3) inferior estimated event-free survival (EFS) at 5 years [58% versus (vs.) 84% in children, 41% vs. 83% in adolescents and 24% vs 63% in young adults], and (4) inferior estimated OS at 5 years [73% vs. 92% in children, 66% vs. 93% in adolescents and 26% vs 75% in young adults [88]. The various genetic abnormalities that are encountered in patients with Ph-like ALL and their targeted therapies are shown in Table 8 [19,[93][94][95][96][97] The investigational targeted therapies in Ph-like ALL are shown in Table 9 [89,98].…”
Section: Philadelphia Chromosome-like Allmentioning
confidence: 99%
“…Unfortunately, Ph-like ALL is essentially heterogeneous and a HR subtype of ALL [19,[92][93][94][95]98]. It has characteristic and distinct genetic mutations and rearrangements that are activated by a diverse array of cytokine receptor and tyrosine kinase signaling [87,89,[92][93][94]96].…”
Section: Philadelphia Chromosome-like Allmentioning
confidence: 99%
See 2 more Smart Citations